Tungsten alloy wire and preparation method and application thereof
By doping rare earth elements and their compounds in tungsten alloys and controlling their distribution, combined with wet doping and pressure processing technology, the crack and wire breaking problem caused by the merger of second phase particles in the high temperature process is solved, and the high tensile strength and excellent processing performance of tungsten alloy wires are achieved.
Patent Information
- Application Number
- CN202411918889.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-26
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing tungsten alloy wires combine and grow during high-temperature sintering and recrystallization annealing, resulting in cracks and wire breakage problems. The breakage of the second phase particles during pressure processing cannot effectively improve the strength of the tungsten matrix.
By doping rare earth elements such as lanthanum, cerium, praseodymium and other compounds in the tungsten alloy, the linear distribution and radial average width are controlled to be less than 5nm, and using wet doping, powdering, pressing, sintering and pressure processing techniques, tungsten alloy wires with excellent mechanical properties are prepared.
The cracks and wire breaks caused by the second phase particles are reduced, and the tensile strength and processing performance of the tungsten alloy wire are improved, so that the wire has a tensile strength of more than 5000 MPa at a wire diameter of 20 to 60 μm.
Smart Images

Figure CN119843132A_ABST
Abstract
Description
[0001] This application claims the priority of the Chinese patent application filed with the China Patent Office on December 26, 2023, with application number 2023118259397 and invention name “A tungsten alloy wire, its preparation method and application”, the entire contents of which are incorporated by reference in this application. Technical Field
[0002] The present application relates to the technical field of tungsten alloy materials, and in particular to a tungsten alloy wire and a preparation method and application thereof. Background Art
[0003] Tungsten-based alloy is an alloy material made of refractory metal tungsten as the hard phase and nickel, iron, copper or silver as the bonding phase through powder metallurgy or injection molding technology. Due to its excellent thermal, mechanical, electrical and chemical properties, it is widely used in automobiles, medical care, aerospace, military, defense and other fields.
[0004] In order to further improve the comprehensive mechanical properties of tungsten alloy wires, rare earth elements or rare earth compounds are currently doped into the tungsten matrix as the second phase dispersion strengthened tungsten material. During high-temperature sintering and recrystallization annealing, solid-liquid phase transition is prone to occur. During the transition process, more second-phase particles will merge and then grow. In addition, during the current pressure processing process, the second-phase particles will break due to uneven forging or drawing deformation, and the strength of the tungsten matrix cannot be effectively improved. More cracks will form at the junction of the second-phase particles and the tungsten wire, causing wire breakage, and also limiting the diameter size of the deep processing of the tungsten wire.
[0005] For example, Chinese patent document CN113186438A discloses an alloy wire and its preparation method and application, wherein the lanthanum oxide content is 0.1wt% to 2.0wt%, and the tensile strength of the alloy wire can reach 4800MPa below 40μm. However, due to the large amount of rare earth oxide added, the wire defects increase sharply, and the proportion of wire breakage failures in the preparation process increases significantly. At the same time, due to the aggregation of rare earth second phases, the deformation resistance of the alloy wire is too large, resulting in a decrease in the strength increase after the wire is refined, and the processing performance deteriorates, which cannot meet the engineering needs. Summary of the invention
[0006] In order to solve the problem that the introduction of the second phase in the prior art leads to many cracks and wire breaks in the tungsten alloy wire, the present application provides a tungsten alloy wire, wherein the tungsten alloy is composed of the following elements in mass fraction: L 0.4-1.1wt%, X 0.001-0.01wt%, Z 0.001-0.25wt%, and the remainder is tungsten and unavoidable impurities; Wherein, L is one or more of lanthanum, cerium, praseodymium, neodymium, gadolinium, and erbium; X is one or more of yttrium, scandium, hafnium, and zirconium; Z includes oxygen; the wire diameter of the wire is 20 to 60 μm, and in the wire, there is linear L or a compound of L along the wire axis, and the radial average width D of the L or the compound of L is ≤5 nm.
[0007] For example, L represents lanthanum, or cerium, or praseodymium, or lanthanum and cerium, or lanthanum and neodymium, or lanthanum and praseodymium, or lanthanum and gadolinium, or cerium and praseodymium, or cerium and neodymium, or praseodymium and gadolinium, or praseodymium and erbium, or neodymium and gadolinium, or lanthanum, cerium and praseodymium, or lanthanum, cerium and erbium, or lanthanum, praseodymium and neodymium, or cerium, praseodymium and neodymium, or praseodymium, neodymium, gadolinium and erbium, etc.; For another example, the mass percentage of L is 0.4% to 1.1%, or 0.4% to 1.0%, or 0.4% to 0.8%, or 0.4% to 0.6%, or 0.4% to 0.5%, or 1.0 to 1.1%, or 0.8% to 1.1%, of course, it can also be 0.4%, 0.41%, 0.5%, 0.55%, 0.6%, 0.8%, 0.86%, 1.0%, 1.05%, etc.; The mass percentage of X is 0.001-0.01%, or 0.001-0.005%, of course, it can also be 0.001%, 0.005%, 0.006%, 0.008%, 0.009%, 0.0099%, etc.; The mass percentage of Z is 0.001% to 0.25%, or 0.001% to 0.05%, or 0.001% to 0.1%, or 0.001% to 0.2%, or 0.005% to 0.1%, or 0.1% to 0.25%, or 0.1% to 0.2%, or 0.05% to 0.2%. Of course, it can also be 0.0009%, 0.001%, 0.005%, 0.01%, 0.015%, 0.02%, 0.05%, 0.1%, 0.15%, 0.2%, etc.
[0008] The wire diameter of the wire is 20-60 μm, such as 20 μm, 28 μm, 30 μm, 38 μm, 40 μm, 48 μm, 50 μm, 55 μm, 58 μm, 60 μm, etc. The tungsten alloy wire may be uniform or incompletely uniform, and may also contain a difference of several percentages such as 1% according to the location; It should be noted that “linear” means that the dimension of L or the compound of L in the wire along the axial direction of the wire is much larger than the dimension along the radial direction of the wire.
[0009] The compounds of L and X can be oxides, such as lanthanum oxide, cerium oxide, praseodymium oxide, neodymium oxide, gadolinium oxide, erbium oxide, yttrium oxide, scandium oxide, hafnium oxide, zirconium oxide, etc. Of course, they can also be other forms of compounds, such as carbide of L and carbide of X.
[0010] In some embodiments, Z also includes one or more of carbon, boron, and nitrogen; when carbon, boron, and nitrogen are present at the same time, the total amount of carbon, boron, and nitrogen does not exceed 0.07%.
[0011] In some embodiments, in the wire, the radial average width of the tungsten grains is ≤80 nm; Preferably, the number of surface defects of the wire is ≤10 / 100 meters; Preferably, the dislocation density in the wire is ≥5*10 9 / mm 2 ; Preferably, the number of L or a compound of L in the wire / the number of tungsten grains=γ, 3≤γ≤10.
[0012] In order to ensure the final strength of the tungsten alloy wire, it is necessary to ensure that the wire has good comprehensive mechanical properties and good processing feasibility. The ratio of the number of L or L compounds in the wire to the number of tungsten grains γ is between 3 and 10. If γ < 3, the breaking force of the wire cannot be met. If γ > 10, the processing performance of the wire will deteriorate sharply, resulting in a sharp increase in cracks in the wire and serious wire breakage.
[0013] Preferably, when the wire diameter is greater than 50 μm and ≤ 60 μm, the radial average width D of L or L compound is ≤ 5 nm, and the wire tensile strength is ≥ 5000 MPa; when the wire diameter is greater than 40 μm and ≤ 50 μm, the radial average width D of L or L compound is ≤ 4 nm, and the wire tensile strength is ≥ 5500 MPa; When the wire diameter is greater than 30 μm and less than or equal to 40 μm, the radial average width D of L or the compound of L is less than or equal to 3 nm, and the tensile strength of the wire is greater than or equal to 6000 MPa; when the wire diameter is greater than or equal to 20 μm and less than or equal to 30 μm, the radial average width D of L or the compound of L is less than or equal to 2 nm, and the tensile strength of the wire is greater than or equal to 7000 MPa; The present application also provides a method for preparing the above-mentioned tungsten alloy wire, including wet doping, powder making, pressing, sintering, blanking and pressure processing.
[0014] In some embodiments, the wet doping process is: evenly dispersing blue tungsten powder in deionized water to obtain a blue tungsten suspension, evenly dispersing nano-scale compound powders of L and X in an alkaline solution with a pH value greater than 11 to form a second suspension, and then sequentially spraying a solution containing the Z element and the second suspension into the blue tungsten suspension, and heating and drying to obtain doped blue tungsten powder.
[0015] Preferably, the nano-scale compound powders of L and X are uniformly dispersed in an alkaline solution with a pH value greater than 11, and then stirred at a high speed of 1000 to 2000 r / min by a stirring device; Preferably, the solution containing the element Z is a salt solution of the element Z or a suspension of a compound containing the element Z; It is preferred that the solution of element Z be diluted to a volume ratio of 1:20 or more; The preferred drying method is rapid vacuum heating drying.
[0016] By preparing a suspension of L and X element compounds, fine particles are directly and evenly doped into the blue tungsten powder, and the fine particles are used as heterogeneous crystal nuclei to co-crystallize and precipitate with tungsten particles. The tungsten alloy powder that can be prepared has a more uniform dispersion distribution. This method no longer requires the use of acid salts of elements, and the range of dispersed particles that can be prepared is wider, and the performance of the obtained tungsten material is more stable and reliable.
[0017] In some embodiments, the preparation method of the blue tungsten powder is: feeding ammonium paratungstate into a reduction furnace, reducing it at 400-600°C under hydrogen and nitrogen protection to obtain blue tungsten powder, wherein the thickness of the ammonium paratungstate powder layer is less than 10mm, the hydrogen flow rate in the reduction furnace is 20-40L / min, the nitrogen flow rate is 80-160L / min, the oxygen index of the blue tungsten powder is 2.85±0.05, and the ammonium tungsten bronze phase component is greater than 80%.
[0018] The production of blue tungsten powder uses hydrogen and nitrogen mixed gas as a reducing protective medium. The performance of the blue tungsten powder is controlled by the thickness of the material layer and the size and flow direction of the hydrogen. The oxygen index of blue tungsten is 2.85±0.05, and the blue tungsten with an ammonium tungsten bronze phase ratio of more than 80% is doped. The blue tungsten has coarse particles and many surface cracks, which is conducive to the entry of rare earth solution and improves the effectiveness of doping, thereby improving the uniformity of the second phase distribution in the tungsten wire and improving the comprehensive mechanical properties and processing performance of the tungsten wire.
[0019] In some embodiments, the powder making process is: reducing the doped blue tungsten powder to obtain alloy powder A with a particle size of 1.5 to 2.6 μm and alloy powder B with a particle size of 3.8 to 4.5 μm, respectively, and then mixing alloy powder A and alloy powder B to obtain a mixed powder; Preferably, the reduction method of the alloy powder A is: reducing the doped blue tungsten powder once in a 500-800° C. hydrogen reduction furnace, and then reducing it twice in a 700-1000° C. hydrogen reduction furnace to obtain alloy powder A with a particle size of 1.5-2.6 μm.
[0020] Preferably, the reduction method of the alloy powder B is: reducing the doped blue tungsten powder in a hydrogen reduction furnace at 700-1100° C. to obtain the alloy powder B with a particle size of 3.8-4.5 μm.
[0021] Preferably, the alloy powder A and the alloy powder B are mixed in a mass ratio of 1:(1-2).
[0022] The fine-grained tungsten alloy powder prepared by double reduction is mixed with the coarse-grained tungsten alloy powder prepared by high-temperature single reduction in a certain proportion. This not only avoids the local uneven doping of the coarse-grained powder during the reduction process, but also effectively inhibits the agglomeration and enrichment of the fine-grained powder after reduction, making the subsequent alloy powder doping micro-uneven, resulting in defects in the subsequent pressure processing process and reducing the risk of wire breakage. In some embodiments, the sintering process is: the pre-sintered blank obtained by pressing is sintered by electricity, and the sintering is carried out in two stages. The first sintering is carried out at 60% of the current intensity of the tungsten bar fusing current for 30 to 45 minutes and then cooled down. The second sintering is carried out at 90% to 92% of the current intensity of the tungsten bar fusing current for 40 to 80 minutes, and the density is 18.6 g / cm 3 The above sintered billets.
[0023] Preferably, the second sintering is carried out in a hydrogen atmosphere, wherein the purity of hydrogen is >99.5%.
[0024] The two-stage high-temperature sintering is different from the traditional one-time high-temperature sintering and the combined sintering mode of power sintering and medium-frequency indirect sintering. The density of the billet obtained by conventional one-time power sintering and vertical melting and medium-frequency combined sintering can only reach 17.2-18.4g / cm 3 , basically below 92% of the theoretical density, and the uniformity of its edge and core tissue is greatly different, that is, the tungsten wire fiber size consistency is poor, which leads to uneven processing tissue in the subsequent tungsten alloy material processing process, making the wire easy to break. This application fully volatilizes the impurity elements in the tungsten billet and closes the surface gaps of the tungsten billet through the first power-on sintering, improves the hydrogen purity and improves the billet density in the second power-on high-temperature sintering, obtains a uniform billet with a density of more than 96%, improves the billet tissue consistency, improves the subsequent tungsten alloy wire fiber consistency, and improves the winding performance of the tungsten alloy wire.
[0025] In some embodiments, the pressure processing process is: the alloy rod obtained by the blanking is recrystallized and annealed, and then forged into a tungsten rod with a diameter of 2.5 to 4.0 mm through a multi-pass continuous rotary forging device, and the tungsten rod is roughly drawn through drawing dies of different specifications, and the drawing passes are repeated for multiple times with a compression ratio of 35% to 60% to obtain a tungsten alloy thick wire with a diameter of 0.3 to 0.5 mm.
[0026] The tungsten alloy wire is processed with a large compression ratio of 35% to 60%, and the obtained wire fiber is more developed, which is conducive to the linearization of L element and its compounds during the processing, thereby improving the breaking force of the wire.
[0027] In some embodiments, during the pressure processing, the alloy rod obtained by the billeting is heated to 2000-2600° C. by a medium / high frequency induction coil for recrystallization annealing.
[0028] In some embodiments, the tungsten alloy wire needs to be annealed when it is drawn to a diameter of 0.3-0.5 mm, and the annealing temperature is 1300-1800°C. After annealing, the tungsten alloy wire is cooled in an oxygen environment, and the annealing is repeated multiple times to obtain tungsten alloy wires of different diameters. When the tungsten alloy wire is drawn to less than 0.3 mm, no annealing is performed. The wire after annealing and cooling is drawn through wire drawing dies of different specifications, and the drawing is repeated multiple times to each wire to the required wire diameter.
[0029] By oxygen cooling the wire after annealing, the content and thickness of the oxide layer on the surface of the tungsten alloy wire can be increased, which can effectively improve the wire lubrication layer, thereby improving the drawing conditions and ensuring the feasibility of wire drawing with a large compression ratio, thereby greatly reducing the probability of wire breakage.
[0030] The present application also provides an application of the above-mentioned tungsten alloy wire in the fields of cutting, cut-resistant protection, cables, screen printing, ropes or textiles.
[0031] Compared with the prior art, the tungsten alloy wire provided in this application has the following advantages: The present application uses one or more rare earth elements / rare earth compounds as the second phase reinforced tungsten material, controls the L element to be doped in a linear form between the tungsten matrix, and makes the radial average width of L less than 5nm, thereby greatly reducing the cracks and wire breaks caused by the second phase particles during the subsequent pressure processing, which is beneficial to ensure the mechanical strength of the tungsten alloy wire, so that the wire has a tensile strength of more than 5000MPa at a wire diameter of 20 to 60μm and a wire diameter of 60μm, while enhancing the processing performance of the tungsten alloy wire. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0033] Figure 1 This is a schematic diagram of measuring the radial average width of L or a compound of L provided in the present application. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0035] The present application provides a tungsten alloy wire, wherein the tungsten alloy is composed of the following elements in mass fraction: L 0.4~1.1wt%, X 0.001~0.01wt%, Z 0.001~0.25wt%, the balance is tungsten and unavoidable impurities; Wherein, L is one or more of lanthanum, cerium, praseodymium, neodymium, gadolinium, and erbium; X is one or more of yttrium, scandium, hafnium, and zirconium; Said Z comprises oxygen; The wire has a wire diameter of 20 to 60 μm. In the wire, there is linear L or a compound of L along the wire axis, and the radial average width D of the L or the compound of L is ≤5 nm.
[0036] It is understandable that unavoidable impurities are other elements introduced during the preparation process.
[0037] The radial average width of tungsten grains is ≤80nm; The number of L or L compounds in the wire / the number of tungsten grains=γ, 3≤γ≤10. When the wire diameter of the wire is greater than 50μm and less than or equal to 60μm, the radial average width D of L or L compounds is less than or equal to 5nm, and the tensile strength of the wire is greater than or equal to 5000MPa; When the wire diameter is greater than 40 μm and less than or equal to 50 μm, the radial average width D of L or the compound of L is less than or equal to 4 nm, and the tensile strength of the wire is greater than or equal to 5500 MPa; When the wire diameter is greater than 30 μm and less than or equal to 40 μm, the radial average width D of L or the compound of L is less than or equal to 3 nm, and the tensile strength of the wire is greater than or equal to 6000 MPa; When the wire diameter is ≥20 μm and ≤30 μm, the radial average width D of L or the compound of L is ≤2 nm, and the tensile strength of the wire is ≥7000 MPa; The number of surface defects of the wire is ≤10 / 100 meters; The dislocation density in the wire is ≥5*10 9 / mm 2 .
[0038] The present application provides a method for preparing tungsten alloy wire, including wet doping, powder making, pressing, sintering, blanking and pressure processing, etc.: The wet doping method comprises: uniformly dispersing blue tungsten powder in deionized water to obtain a blue tungsten suspension, uniformly dispersing nanometer-scale compound powders of L and X in an alkaline solution with a pH value greater than 11 to form a second suspension, and then sequentially spraying a solution containing the Z element and the second suspension into the blue tungsten suspension, and performing rapid vacuum heating and drying after spraying to obtain doped blue tungsten powder; The preparation method of the blue tungsten powder is as follows: ammonium paratungstate is fed into a reduction furnace, and is reduced at 400-600° C. under the protection of hydrogen and nitrogen to obtain blue tungsten powder, wherein the thickness of the ammonium paratungstate powder layer is less than 10 mm, the hydrogen flow rate in the reduction furnace is 20-40 L / min, the nitrogen flow rate is 80-160 L / min, the oxygen index of the blue tungsten powder is 2.85±0.05, and the ammonium tungsten bronze phase component is greater than 80%; The powder making process comprises: reducing the doped blue tungsten powder in a hydrogen reduction furnace at 500-800° C. for a primary reduction, and then reducing the doped blue tungsten powder in a hydrogen reduction furnace at 700-1000° C. for a secondary reduction, to obtain alloy powder A with a particle size of 1.5-2.6 μm; The doped blue tungsten powder is reduced in a hydrogen reduction furnace at 700-1100° C. to obtain alloy powder B with a particle size of 3.8-4.5 μm; The alloy powder A and the alloy powder B are mixed in a mass ratio of 1:(1-2) to obtain a mixed powder; The sintering is as follows: the pre-sintered blank obtained by pressing is sintered by electricity, and the sintering is carried out in two stages. The first sintering is carried out at a current intensity of 60% of the tungsten bar fusing current for 30 to 45 minutes and then the temperature is lowered. The second sintering is carried out at a current intensity of 90% to 92% of the tungsten bar fusing current for 40 to 80 minutes to obtain a density of 18.6 g / cm 3 The above sintered billet; Preferably, the second sintering is carried out in a hydrogen atmosphere, wherein the purity of hydrogen is > 99.5%; The pressure processing is as follows: the alloy rod obtained by the blanking is heated to 2000-2600° C. by a medium / high frequency induction coil for recrystallization annealing, and then forged into a tungsten rod with a diameter of 2.5-4.0 mm by a multi-pass continuous rotary forging device; The tungsten rod is roughly drawn through wire drawing dies of different specifications, and the drawing passes are repeated for multiple times with a compression ratio of 35% to 60% to obtain a tungsten alloy thick wire with a diameter of 0.3 to 0.5 mm; The tungsten alloy wire needs to be annealed when it is drawn to a diameter of 0.3-0.5 mm, and the annealing temperature is 1300-1800° C. After annealing, the tungsten alloy wire is cooled in an oxygen environment.
[0039] The annealed and cooled wire is drawn through wire drawing dies of different specifications, and the drawing process is repeated multiple times to reach the required wire diameter.
[0040] In addition, the pressing and blanking steps in the above steps are preferably, but not limited to, implemented in the following manner, namely: Pressing: The mixed powder is pressed into a green compact with a single weight of 1.5 to 6 kg at a pressure of 140 to 240 MPa by isostatic pressing, and the green compact is pre-sintered at a low temperature of 1200 to 1400°C for 10 to 30 minutes in a hydrogen atmosphere to increase the green compact strength; Billeting: The sintered billet strips with a diameter of 15 to 25 mm are billeted into alloy rods with a diameter of 8.0 to 12.0 mm by continuous rolling at 1600 to 1700°C using a multi-roll rolling mill.
[0041] The preparation method also includes an electrolytic cleaning post-treatment step to facilitate subsequent electroplating operations.
[0042] To this end, the present application provides the tungsten alloy element composition of the embodiment and comparative example shown in Table 1 below: Table 1 (unit: wt%):
[0043] Among them, “-” means that the corresponding element is not added.
[0044] Example 1.1 This embodiment is a tungsten alloy wire prepared according to the present application, and its material element composition includes: 0.15wt% cerium, 0.25wt% erbium, 0.006wt% yttrium, 0.001wt% carbon, 0.094wt% oxygen, and the balance is tungsten and unavoidable impurities; The preparation steps are as follows: Step 1, preparation of blue tungsten: the ammonium paratungstate powder is reduced by hydrogen in a reverse hydrogen continuous reduction furnace at 400°C, 450°C, 500°C and 560°C, the ammonium paratungstate powder layer thickness is 6mm, the hydrogen flow rate is 20L / min, the nitrogen flow rate is 160L / min, and blue tungsten powder is obtained, the oxygen index is 2.8, and the ammonium tungsten bronze phase component is 82%; Step 2, wet doping: the blue tungsten powder obtained in step 1 is uniformly dispersed in deionized water to obtain a blue tungsten suspension, wherein the volume ratio of the blue tungsten powder to the deionized water is 1:15; an appropriate amount of carbon powder and deionized water are mixed at a mass ratio of 1:20 to obtain a first suspension, an appropriate amount of nano-powders of cerium oxide, erbium oxide and yttrium oxide are uniformly dispersed in a sodium hydroxide solution with a pH of 12, and stirred at a high speed of 2000r / min in a high-speed emulsifying device to form a second suspension, and then the first suspension and the second suspension are sprayed into the blue tungsten suspension through a vacuum pipe in turn, and after the spraying is completed, rapid vacuum heating and drying are performed to obtain doped blue tungsten powder; Step 3, powder making: the doped blue tungsten powder obtained in step 2 is reduced once in a three-temperature zone hydrogen reduction furnace at 500°C, 650°C, and 750°C, and then reduced twice in a four-temperature zone hydrogen reduction furnace at 700°C, 810°C, 870°C, and 920°C to obtain alloy powder A with a particle size of 1.5 μm; The doped blue tungsten powder obtained in step 2 is reduced in a four-temperature zone hydrogen reduction furnace at 720° C., 820° C., 870° C., and 950° C. to obtain alloy powder B with a particle size of 4.5 μm; Alloy powder A and alloy powder B are placed in a high-energy powder mixer at a ratio of 1:1, and mixed for 100 minutes to obtain a mixed powder; Step 4, pressing: the mixed powder obtained in step 3 is pressed into a green compact with a single weight of 3 kg at a pressure of 160 MPa by isostatic pressing, and the green compact is pre-sintered at 1300° C. in a hydrogen atmosphere for 20 minutes to obtain a pre-sintered green compact; Step 5, sintering: the pre-sintered blank obtained in step 4 is sintered by electricity. The sintering is carried out in two stages. The first sintering is carried out at a current intensity of 60% of the tungsten bar fusing current for 45 minutes, then the temperature is lowered, the vertical melting cover is purged and dried, and the second sintering is carried out at a current intensity of 92% of the tungsten bar fusing current for 80 minutes to obtain a density of 18.68g / cm 3 Sintered billet; Step 6, blanking: using a multi-roll rolling mill to continuously roll the sintered billet with a diameter of 20 mm into an alloy rod with a diameter of 8.0 mm at a heating temperature of 1600° C.; Step 7, pressure processing: the alloy rod obtained in step 6 is heated to 2600° C. by a medium frequency induction coil for recrystallization annealing, and then forged into a tungsten rod with a diameter of 4.0 mm by a multi-pass continuous rotary forging device; Step 8, the tungsten rod is roughly drawn through wire drawing dies of different specifications, and the drawing passes are repeated for multiple times with a compression ratio of 35% to 60% to obtain a tungsten alloy thick wire with a diameter of 0.5 mm; Step 9, annealing: the tungsten alloy wire obtained in step 8 is annealed when it is processed to φ0.5 mm, and the tungsten alloy wire is cooled in an oxygen environment after annealing, wherein the annealing temperature is 1600° C. when the diameter is φ0.5 mm; Step 10, drawing the annealed wire obtained in step 9 through wire drawing dies of different specifications, and repeatedly drawing the wire to diameters of 58 μm, 48 μm, 38 μm, 28 μm, and 20 μm respectively; Step 11, electrolytic cleaning: The tungsten alloy wire obtained in step 10 is first electrolyzed by a 30wt% potassium hydroxide solution, which includes 8 groups of AC electrolytic sheets, and then sequentially electrolyzed by 8 groups of 5wt% potassium hydroxide solutions, which include 10 groups of DC electrolytic sheets. The electrolysis speed is 180m / min. After electrolysis, the surface is cleaned with deionized water to obtain white fine tungsten wires of different wire diameters.
[0045] Example 1.2 The difference between this embodiment and embodiment 1.1 is that its material element composition includes 0.55wt% cerium, 0.55wt% erbium, 0.01wt% yttrium, 0.035wt% carbon, 0.215wt% oxygen, and the remainder is tungsten and unavoidable impurities; the remaining preparation steps are the same as embodiment 1.1.
[0046] Comparative Example 1.1 The material element composition includes: 0.8wt% lanthanum, 0.138wt% oxygen, and the balance is tungsten and unavoidable impurities; The preparation steps are as follows: Step 1, doping: evenly dope an appropriate amount of lanthanum nitrate solution into the blue tungsten powder, stir it thoroughly, and then dry it at a low temperature of 80°C for 4 hours and then at a high temperature of 120°C; Step 2, reduction: the material obtained in step 1 is reduced into alloy powder of suitable particle size in a four-temperature zone reduction furnace; Step 3, powder mixing: put the materials obtained in step 2 into a powder mixer according to different particle sizes. Mix the powder for 80 minutes at a speed of 8 rpm; Step 4, powder pressing: the powders of different particle sizes are pressed into a green compact with a single weight of 3.0 kg at a pressure of 200 MPa by isostatic pressing, and the green compact is pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact; Step 5: High temperature sintering: high temperature sintering is performed to obtain a density of 18.10 g / cm 3 Sintered billet; Step 6, blanking: using a multi-roll rolling mill to continuously roll the 23.0 mm diameter sintered billet into an 8.0 mm alloy rod at a heating temperature of 1650° C.; Step 7, pressure processing: multiple passes of rotary forging are used. Then drawing is performed through wire drawing dies of different specifications, and after repeated drawing, alloy wires with diameters of 58μm, 48μm, 38μm, 28μm, and 20μm are produced respectively.
[0047] Comparative Example 1.2 The material element composition includes: 0.8wt% cerium, 0.183wt% oxygen, and the balance is tungsten and unavoidable impurities; The preparation steps are as follows: Step 1, doping: evenly dope an appropriate amount of lanthanum nitrate solution into the blue tungsten powder, stir it thoroughly, and then dry it at a low temperature of 80°C for 4 hours and then at a high temperature of 120°C; Step 2, reduction: the material obtained in step 1 is reduced into alloy powder of suitable particle size in a four-temperature zone reduction furnace; Step 3, powder mixing: put the materials obtained in step 2 into a powder mixer according to different particle sizes. Mix the powder for 80 minutes at a speed of 8 rpm; Step 4, powder pressing: the powders of different particle sizes are pressed into a green compact with a single weight of 3.0 kg at a pressure of 200 MPa by isostatic pressing, and the green compact is pre-sintered at a low temperature in a hydrogen atmosphere to increase the strength of the green compact; Step 5: High temperature sintering: high temperature sintering is performed to obtain a density of 18.10 g / cm 3 Sintered billet; Step 6, blanking: using a multi-roll rolling mill to continuously roll the 23.0 mm diameter sintered billet into an 8.0 mm alloy rod at a heating temperature of 1650° C.; Step 7, pressure processing: multiple passes of rotary forging are used. Then drawing is performed through wire drawing dies of different specifications, and after repeated drawing, alloy wires with diameters of 58μm, 48μm, 38μm, 28μm, and 20μm are produced respectively.
[0048] Comparative Example 1.3 (total content of Z element exceeds 0.25wt%) The difference from Example 1.1 is that its material element composition includes 0.15wt% cerium, 0.25wt% erbium, 0.006wt% yttrium, 0.176wt% carbon, 0.076wt% oxygen, and the remainder is tungsten and unavoidable impurities; the remaining preparation steps are the same as Example 1.1.
[0049] Comparative Example 1.4 (the total content of the L element second phase exceeds 1.1 wt%) The difference from Example 1.1 is that its material element composition includes 0.45wt% cerium, 0.75wt% erbium, 0.006wt% yttrium, 0.001wt% carbon, 0.223wt% oxygen, and the remainder is tungsten and unavoidable impurities; the remaining preparation steps are the same as Example 1.1.
[0050] Comparative Example 2.1 (using deionized water as the solvent for element L) The material element composition is the same as that of Example 1.1. The difference between Comparative Example 2.1 and Example 1.1 is that: Step 2, wet doping is as follows: the blue tungsten powder obtained in step 1 is evenly dispersed in deionized water to obtain a blue tungsten suspension, wherein the volume ratio of the blue tungsten powder to the deionized water is 1:15; an appropriate amount of carbon powder and deionized water are mixed at a mass ratio of 1:20 to obtain a first suspension, an appropriate amount of crystalline powders of cerium nitrate, erbium nitrate and yttrium nitrate are evenly dispersed in deionized water, and stirred at a high speed of 2000r / min in a high-speed emulsifying device to form a second suspension, and then the first suspension and the second suspension are added to the blue tungsten suspension in turn, and they are fully stirred and dried to obtain doped blue tungsten, the stirring speed is 40r / min, and the drying temperature is 160°C; the remaining steps are the same as Example 1.1.
[0051] Comparative Example 2.2 (Alloy powder prepared by single reduction) The material element composition is the same as that of Example 1.1. The difference between Comparative Example 2.2 and Example 1.1 is that: Step 3, powder making is as follows: reduce the doped blue tungsten powder obtained in step 2 in a four-temperature zone hydrogen reduction furnace at 650°C, 750°C, 850°C, and 930°C, with a reduction rate of 20 min / boat, to obtain an alloy powder with a particle size of 3.0 μm; the remaining steps are the same as in Example 1.1.
[0052] Comparative Example 2.3 (using conventional drawing pass compression ratio of 10% to 30%) The material element composition is the same as that of Example 1.1. The difference between Comparative Example 2.3 and Example 1.1 is that: Step 8, the tungsten rod is roughly drawn through wire drawing dies of different specifications, and the drawing passes are repeated for multiple times with a compression ratio of 10% to 30% to obtain a tungsten alloy thick wire with a diameter of 0.5 mm; the remaining steps are the same as in Example 1.1.
[0053] Comparative Example 2.4.1 (Cooling in air after annealing) The material element composition is the same as that of Example 1.1. The difference between Comparative Example 2.4.1 and Example 1.1 is that: Step 9, annealing: the tungsten alloy wire obtained in step 8 is annealed when it is processed to φ0.5 mm, and the tungsten alloy wire is cooled in an air environment after annealing, wherein the annealing temperature is 1600° C. when it is φ0.5 mm; the remaining steps are the same as those in Example 1.1.
[0054] Comparative Example 2.4.2 (Cooling in air after annealing) The material element composition is the same as that of Example 1.1. The difference between Comparative Example 2.4.2 and Example 1.1 is that: Step 9, annealing: the tungsten alloy wire obtained in step 8 is annealed when it is processed to φ0.5 mm, and the tungsten alloy wire is cooled in an air environment after annealing, wherein the annealing temperature is 1650° C. when φ0.5 mm; the remaining steps are the same as in Example 1.1.
[0055] Comparative Example 2.4.3 (Cooling in air after annealing) The material element composition is the same as that of Example 1.1. The difference between Comparative Example 2.4.3 and Example 1.1 is that: Step 9, annealing: the tungsten alloy wire obtained in step 8 is annealed when it is processed to φ0.5 mm, and the tungsten alloy wire is cooled in an air environment after annealing, wherein the annealing temperature is 1700° C. when it is φ0.5 mm; the remaining steps are the same as in Example 1.1.
[0056] Comparative Example 2.4.4 (Cooling in air after annealing) The material element composition is the same as that of Example 1.1. The difference between Comparative Example 2.4.4 and Example 1.1 is that: Step 9, annealing: the tungsten alloy wire obtained in step 8 is annealed when it is processed to φ0.5 mm, and the tungsten alloy wire is cooled in an air environment after annealing, wherein the annealing temperature is 1550° C. when the diameter is φ0.5 mm; the remaining steps are the same as those in Example 1.1.
[0057] Microstructure and performance testing The tungsten alloy wires obtained in the embodiment and the comparative example were subjected to a tensile strength test and characterized using a transmission electron microscope, and the γ value was calculated. The test results are shown in Table 2-3.
[0058] The tungsten alloy wire obtained in the embodiment and the comparative example was cut into thin slices along the axial direction of the tungsten alloy wire using a focused ion beam cutting device, and the thin slices were placed in a high-resolution transmission electron microscope and characterized using different modes to observe the number of linear second phases and the number of tungsten grains in the sample thin slices, and the γ value was calculated.
[0059] The calculation formula of γ value is: γ = number of linear second phases / number of tungsten grains.
[0060] Among them, the tensile strength test method is: using a standard tensile machine, taking a 200mm long tungsten wire to clamp, loading at one end at a constant speed, and obtaining the breaking force data; The tensile strength is calculated by the following formula: σ=F / S, Where, F is the breaking force, N; S is the original cross-sectional area, mm; Table 2
[0061] Among them, “ / ” means there is no corresponding data.
[0062] The number of surface defects, the average diameter of tungsten grains, the radial average width of L or L compounds and the dislocation density of the tungsten alloy wires obtained in the examples and comparative examples were measured. The measurement results are shown in Table 3: The method for measuring the number of surface defects is as follows: the obtained tungsten alloy wire is tested for surface defects by an eddy current flaw detector, and the depth of the flaw detection signal exceeding 15% of the diameter is defined as a defect; The radial average width of tungsten grains is measured as follows: a thin slice is cut along the axial direction of the wire using a focused ion beam cutting device, the thin slice is placed in a scanning electron microscope with an EBSD (EBSD) to collect the morphology of the tungsten grains of the sample to be tested, and the width of the upper and lower grain boundaries is measured using conventional measurement software to obtain the radial width of the tungsten grains. The average value of the measured widths of multiple tungsten grains is the radial average width of the tungsten grains.
[0063] The radial mean width of a compound of L or L is measured as: Figure 1 As shown, a focused ion beam cutting device is used to cut a thin slice along the axial direction of the tungsten alloy wire 1, and the thin slice is placed in a high-resolution transmission electron microscope. The morphology is first observed in the bright and dark field mode, and the position with obvious contrast in the morphology is selected for surface scanning, and a line scan is performed perpendicular to the axial position of the tungsten alloy wire to obtain the element distribution and element composition information. The position with obvious contrast and obvious difference in element distribution in the sample is photographed by a transmission electron microscope (that is, the position of the aggregation area of each element of the second phase) to obtain a high-resolution image of the second phase, and the high-resolution image is Fourier transformed to obtain a lattice diffraction spectrum. The obtained second-phase diffraction spectrum is combined with the second-phase element composition information to calibrate the physical phase corresponding to each diffraction spectrum. By comparing the physical phase card, after confirming that the compound phase structure is L or L, the software measures the compound width of L or L; Figure 1 In the figure, 10 represents the tungsten matrix, 20 represents L or a compound of L, and the average value is calculated by measuring the widths of multiple Ls, that is, the radial average width of L or the compound of L. It can be understood that for the sake of convenience, Figure 1 What is captured is a partial cross section of the tungsten alloy wire sheet, not the entire sheet.
[0064] The test method for dislocation density is: use focused ion beam cutting equipment to cut a thin slice along the axial direction of the tungsten alloy wire, place the thin slice in a high-resolution transmission electron microscope to directly observe the lattice pattern, obtain the dislocation, and calculate the number of dislocation lines passing through the unit cross-sectional area to obtain the dislocation density.
[0065] Table 3
[0066] Among them, “ / ” means there is no corresponding data.
[0067] From the test results in Table 2 and Table 3, we can see that: The tungsten alloy wire provided in the embodiment of the present application has a tensile strength of more than 5000 MPa at a wire diameter of 20 to 60 μm, and as the wire diameter decreases, its tensile strength increases accordingly. At 28 μm, its tensile strength can reach more than 7000 MPa, and the number of surface defects of the wire is less than 10 / 100 meters; at 28 μm, L or L compounds exist in a linear form, and their radial average width is less than 4 nm, the radial average width of tungsten grains is less than 80 nm, and the dislocation density in the wire is greater than 5*10 9 / mm 2 , the number of L or L compounds in the wire / the number of tungsten grains = γ, 3≤γ≤10.
[0068] From the comparison results of Comparative Examples 1.1 and 1.2 with Example 1.1, it can be seen that: Compared with the existing process, the tungsten alloy wire preparation method provided in the present application can effectively improve the tensile strength of the wire. The reason is that the single L element second phase merges and grows during the high-temperature sintering and recrystallization annealing process, resulting in a wider radial average width of the L element, and more cracks and wire breaks caused by the second phase particles during the subsequent pressure processing, which affects the mechanical strength and processing performance of the tungsten alloy wire. With the sharp increase in cracks, the wire breakage during the wire drawing process increases significantly. From the data in Table 3, it can be seen that with the sharp increase in the number of surface defects on the wire, the wire processing performance deteriorates, and the average number of meters per coil of wire drops sharply; From the comparison results of Comparative Example 1.3 and Example 1.1, it can be seen that: When the Z element content in the tungsten alloy component exceeds 0.25wt%, the Z element forms a solid solution with W, which effectively increases the lattice distortion of tungsten and improves the deformation rate of the tungsten wire, thereby improving the tensile strength of the tungsten wire. However, the introduction of too much Z element will cause the dislocation density of the tungsten alloy wire to increase significantly during the deformation process, resulting in too fast work hardening of the tungsten alloy wire, making it difficult to refine the wire to less than 60μm.
[0069] From the comparison results of Comparative Example 1.4 and Example 1.1, it can be seen that: When the total content of the two L element second phases in the tungsten alloy component exceeds 1.1wt%, the amount of second phases in the tungsten alloy wire is too much, and the ratio γ of the amount of second phases to the amount of tungsten grains is too high, resulting in insufficient bonding between the grains of the tungsten alloy wire. At the same time, the increase in the amount of second phases will greatly increase the difficulty of dislocation slip, resulting in increased difficulty in processing the tungsten alloy wire and making it impossible to process it below 60μm.
[0070] From the comparison results of Comparative Example 2.1 and Example 1.1, it can be seen that: Compared with the embodiment of the present application, when deionized water is used as the solvent of the L element in the wet doping step, the tungsten grain size and the average radial width of L increase at the same wire diameter level. The reason is that the dispersion of the L element compound in the doping process is insufficient, which leads to local enrichment of the L element during the nucleation process of the tungsten powder in the subsequent reduction process. After high-temperature sintering, these L element compounds swallow up each other and grow, resulting in a significant reduction in the strengthening and refinement effect of the actual tungsten grains, and a significant increase in the number of surface defects of the obtained tungsten alloy wire.
[0071] From the comparison results of Comparative Example 2.2 and Example 1.1, it can be seen that: When the alloy powder is prepared by single reduction in the powder making step, the radial average width of L is significantly increased, and the number of surface defects of the prepared tungsten alloy wire is significantly increased, resulting in the tensile strength of the wire being much lower than that of Example 1.1. The reason is that the tungsten alloy powder prepared by high-temperature single reduction is prone to local uneven doping during the reduction process, or agglomeration and enrichment after reduction, which makes the subsequent alloy powder doping microscopically uneven, resulting in defects in the subsequent pressure processing process and reducing the risk of wire breakage.
[0072] From the comparison results of Comparative Example 2.3 and Example 1.1, it can be seen that: When the conventional drawing pass compression ratio of 10% to 30% is used in the pressure processing step, the average radial width of L in the wires of various specifications obtained is larger, and the average width of the tungsten grains is greatly increased, resulting in more cracks and wire breaks caused by second phase particles in the subsequent pressure processing process, which in turn affects the tensile strength.
[0073] It is explained that the present application adopts a large compression ratio of 35% to 60% for tungsten alloy wire processing, and the obtained wire fiber is more developed, which is conducive to the linearization of L element and its compounds during the processing. At the same time, the deformation degree of tungsten grain boundaries is faster, thereby improving the tensile strength of the wire.
[0074] The number of surface defects and the average length of the tungsten alloy wires obtained in Example 2.4.1-2.4.4 were measured. The measurement results are shown in Table 4.
[0075] Table 4
[0076] From the comparison results of Comparative Examples 2.4.1-2.4.4 and Example 1.1, it can be seen that: When the mass percentage of oxide on the wire surface in the annealing step is less than 1%, the tungsten alloy wire undergoes multiple drawing processes after annealing, resulting in a significant increase in the hardening rate of the wire surface due to insufficient surface lubrication layer, which leads to a significant increase in the number of surface defects, and ultimately the product cannot be stably produced to meet the required length. The mass percentage of oxide on the surface of the tungsten alloy wire in this application is greater than or equal to 1%.
[0077] Finally, it should be noted that: The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A tungsten alloy wire, characterized in that: The tungsten alloy is composed of the following elements in mass fraction: L 0.4-1.1wt%, X 0.001-0.01wt%, Z 0.001-0.25wt%, and the remainder is tungsten and unavoidable impurities; Wherein, L is one or more of lanthanum, cerium, praseodymium, neodymium, gadolinium, and erbium; X is one or more of yttrium, scandium, hafnium, and zirconium; Said Z comprises oxygen; The wire has a wire diameter of 20 to 60 μm. In the wire, there is linear L or a compound of L along the wire axis, and the radial average width D of the L or the compound of L is ≤5 nm.
2. The tungsten alloy wire according to claim 1, characterized in that: The Z further comprises one or more of carbon, boron and nitrogen.
3. The tungsten alloy wire according to claim 1, characterized in that: In the wire, the radial average width of the tungsten grains is ≤80nm; The number of L or the compound of L in the wire / the number of tungsten grains=γ, 3≤γ≤10.
4. The tungsten alloy wire according to claim 1, characterized in that: When the wire diameter is greater than 50 μm and less than or equal to 60 μm, the radial average width D of L or the compound of L is less than or equal to 5 nm, and the tensile strength of the wire is greater than or equal to 5000 MPa; When the wire diameter is greater than 40 μm and less than or equal to 50 μm, the radial average width D of L or the compound of L is less than or equal to 4 nm, and the tensile strength of the wire is greater than or equal to 5500 MPa; When the wire diameter is greater than 30 μm and less than or equal to 40 μm, the radial average width D of L or the compound of L is less than or equal to 3 nm, and the tensile strength of the wire is greater than or equal to 6000 MPa; When the wire diameter is ≥20 μm and ≤30 μm, the radial average width D of L or the compound of L is ≤2 nm, and the tensile strength of the wire is ≥7000 MPa.
5. The tungsten alloy wire according to claim 1, characterized in that: The number of surface defects of the wire is ≤10 / 100 meters.
6. The tungsten alloy wire according to claim 1, characterized in that: The dislocation density in the wire is ≥5*10 9 / mm 2 .
7. A method for preparing a tungsten alloy wire according to any one of claims 1 to 6, characterized in that: Including wet doping, powder making, pressing, sintering, blanking and pressure processing.
8. The method for preparing tungsten alloy wire according to claim 7, characterized in that: The wet doping process is as follows: blue tungsten powder is uniformly dispersed in deionized water to obtain a blue tungsten suspension, nanometer-scale compound powders of L and X are uniformly dispersed in an alkaline solution with a pH value greater than 11 to form a second suspension, and then a solution containing the Z element and the second suspension are sequentially sprayed into the blue tungsten suspension, and doped blue tungsten powder is obtained after heating and drying; The powder making process is: reducing the doped blue tungsten powder to obtain alloy powder A with a particle size of 1.5 to 2.6 μm and alloy powder B with a particle size of 3.8 to 4.5 μm, respectively, and then mixing the alloy powder A and the alloy powder B to obtain a mixed powder; The sintering process is as follows: the pre-sintered blank obtained by pressing is sintered by electricity, and the sintering is carried out in two stages. The first sintering is carried out at 60% of the current intensity of the tungsten bar fusing current for 30 to 45 minutes and then cooled down. The second sintering is carried out at 90% to 92% of the current intensity of the tungsten bar fusing current for 40 to 80 minutes to obtain a density of 18.6 g / cm 3 The above sintered billet; The pressure processing process is as follows: the alloy rod obtained by the blanking is recrystallized and annealed, and then forged into a tungsten rod with a diameter of 2.5-4.0 mm through a multi-pass continuous rotary forging device, and the tungsten rod is roughly drawn through wire drawing dies of different specifications, and the drawing passes are repeated for multiple times with a compression ratio of 35% to 60% to obtain a tungsten alloy thick wire with a diameter of 0.3-0.5 mm.
9. The method for preparing tungsten alloy wire according to claim 8, characterized in that: In the wet doping process, the preparation method of the blue tungsten powder is as follows: ammonium paratungstate is fed into a reduction furnace, and reduced at 400-600° C. under the protection of hydrogen and nitrogen to obtain blue tungsten powder, wherein the ammonium paratungstate powder layer thickness is less than 10 mm, the hydrogen flow rate in the reduction furnace is 20-40 L / min, the nitrogen flow rate is 80-160 L / min, the oxygen index of the blue tungsten powder is 2.85±0.05, and the ammonium tungsten bronze phase component is greater than 80%; In the powder making process, the reduction method of the alloy powder A is: the doped blue tungsten powder is reduced once in a hydrogen reduction furnace at 500-800° C., and then reduced twice in a hydrogen reduction furnace to obtain an alloy powder A with a particle size of 1.5-2.6 μm; the reduction method of the alloy powder B is: the doped blue tungsten powder is reduced in a hydrogen reduction furnace at 700-1100° C. to obtain an alloy powder B with a particle size of 3.8-4.5 μm; the alloy powder A and the alloy powder B are mixed in a mass ratio of 1: (1-2); During the pressure processing, the alloy rod obtained by the blanking is heated to 2000-2600°C by a medium / high frequency induction coil for recrystallization annealing; the tungsten alloy wire needs to be annealed when it is drawn to a diameter of 0.3-0.5 mm, and the annealing temperature is 1300-1800°C. After annealing, the tungsten alloy wire is cooled in an oxygen environment, and after annealing, it is repeatedly drawn multiple times to obtain tungsten alloy wires of different diameters.
10. Use of the tungsten alloy wire according to any one of claims 1 to 6 in the fields of cutting, cutting resistance protection, cables, screen printing, ropes or textiles.
Citation Information
Patent Citations
Alloy wire and preparation method and application thereof
CN113186438A
Alloy wire rod and preparation method and application thereof
CN113215463A
Tungsten alloy wire and preparation method thereof
CN114855046A
Preparation method of tungsten-lanthanum alloy wire
CN116460295A
Tungsten alloy doped wire rod
CN116855809A